(untitled) (Al-Academy, 2023)
A collection of pictures of traditional Kurdish women’s national clothing and contemporary clothing was collected. A visit was also made to the city of Sulaymaniyah and the city of Halabja to find out the foundations of traditional clothing for the Kurdish regions and the impact of contemporary fashion on traditional dress. Which represents the culture and regionalism and reflects the picturesque nature of northern Iraq, and in order to complete the study, the parametric measurements of the clothes were analyzed and the graphs of the dress and its accessories were re-drawn to understand and make a comparison between them to study the clear influences and changes and examine the possibility of benefiting from them in sewing contemporary fashion young women and ensure that they do not abandon their traditional dress.